Residual reliability of a composite material subjected to buckling and post-buckling tests: the case of reinforced concrete - Ngnassi Djami, Aslain Brisco; Nguelcheu, Ulrich Ngnassi; Offole, Florence (Frontiers in Mechanical Engineering, 2024)
This article examines the residual reliability of composite materials, focusing on reinforced concrete subjected to buckling and post-buckling tests, a crucial topic in civil engineering. The main aim of the study is to assess how these loads affect mechanical properties, including compressive strength and elongation at break, while identifying associated failure mechanisms. A rigorous methodology was adopted, involving experimental tests on reinforced concrete samples, followed by microscopic analysis and comparison with literature data. The results reveal a significant decrease in compressive strength and modulus of elasticity with increasing loads and loading cycles. In addition, the study highlights a reduction in elongation at break, indicating a loss of ductility and stiffness of the material. Failure mechanisms observed include cracking and delamination, suggesting that the residual reliability of reinforced concrete is inferior to that of advanced composites. These findings underline the importance of appropriate design to ensure the durability of reinforced concrete structures, taking into account the impact of extreme loads and environmental conditions. This research contributes to a better understanding of the behavior of composite materials under critical conditions, providing recommendations for improving design and construction practices in civil engineering.